The Relationship between Perception and Anxiety in HIV Patients at the Victory Plus Foundation in Yogyakarta - Andri Setyorini; Sekar Sari (Jurnal Ilmiah Keperawatan Indonesia (JIKI), 2021)
Perception is the last process of observation which  initiated by the sensory process, namely the process of receiving a stimulus by the senses, then there is attention, then it  passed on to the brain, and only then the person realizes. HIV / AIDS is a dangerous chronic disease. It is undeniable that HIV / AIDS is not only a health problem, but also a problem and consequences on social, spiritual, and psychological aspects. Objective: To analyze the relationship between perceptions and anxiety in HIV patients at Yayasan Victory Plus Yogyakarta. The research design used a correlational study with a cross sectional approach.  Population of patients in this study were 30 HIV patients who received assistance at the Yogyakarta Victory Plus Foundation. The sampling technique used in this study was total sampling, as well as statistical tests used by Kendall's Tau. The results showed a significant relationship between perceptions and anxiety in HIV patients at Yayasan Victory Plus Yogyakarta, with a p value of 0.000 (p <0.01) and Kendall's Tau correlation coefficient of -, 894 **. There is a significant relationship between perceptions and anxiety in HIV patients where the negative correlation results mean that the higher the perception, the more normal anxiety in HIV patients.Key words: HIV patients; Perception; Worry